COMPUTER MODELING OF CHITOSAN ADSORPTION ON A CARBON NANOTUBE - Azimov J.T. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article presents the results of modeling the process of adsorption of chitosan oligomer on a carbon nanotube (CNT). The results of calculating the structural properties of the monomer and dimer of chitosan using the density functional method to obtain optimal geometric parameters and charge distribution of chitosan are presented. Then, using classical molecular dynamics, the binding energy of the chitosan molecule and CNT is calculated. It is established that the nature of the interaction between the chitosan molecule and CNT is specific.